2022
DOI: 10.1177/21925682221083909
|View full text |Cite|
|
Sign up to set email alerts
|

Single Position Lateral Lumbar Interbody Fusion With Posterior Instrumentation Utilizing Computer Navigation and Robotic Assistance: Retrospective case review and surgical technique considerations

Abstract: Study Design Retrospective cohort study. Objective To determine safety and short-term outcomes of single-position lateral lumbar interbody fusion (LLIF) with bilateral posterior instrumentation and robotic assistance. The article also describes surgical technique considerations for the procedure. Methods 20 patients underwent single-position LLIF with posterior instrumentation and robotic assistance. The patients were followed for a minimum of 3 months post-operatively. Results Average operative time was 211 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In most operating rooms, the flip from lateral decubitus to prone can add significant operative time to the surgery resulting in extended anaesthesia usage and increased hospital costs. Several workarounds have been created to improve efficiency in the lateral position, including standalone interbodies, lateral plate fixation, and unilateral pedicle screws [6,7]. Although possible, these workarounds have not come into general favour with the larger spine community.…”
Section: Introductionmentioning
confidence: 99%
“…In most operating rooms, the flip from lateral decubitus to prone can add significant operative time to the surgery resulting in extended anaesthesia usage and increased hospital costs. Several workarounds have been created to improve efficiency in the lateral position, including standalone interbodies, lateral plate fixation, and unilateral pedicle screws [6,7]. Although possible, these workarounds have not come into general favour with the larger spine community.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the application of robot-assisted navigated pedicle screw placement for 360-degree surgeries in a single positioning, Sinkov et al reported limitations regarding contralateral pedicle screw placement due to problems accessing the surgical site in lateral decubitus positioning ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sellin et al applied CT-guided navigation for simultaneous lateral interbody fusion and pedicle screw placement in lateral positioning showing reduced radiation exposure and reduced duration of surgery, especially as intraoperative navigation replaced intraoperative fluoroscopy and therefore allowed the parallel execution of both procedures (32). Ikuma et al compared singlepositioning surgery in a right lateral decubitus positioning for cases with and without spinal navigation, showing a significantly reduced duration of surgery for cases with spinal navigation as spinal navigation partially enabled simultaneous anterior and posterior instrumentation (33).…”
Section: Spinal Navigationmentioning
confidence: 99%
“…For screw application, the robotic arm moves along the preplanned trajectory with precision, enabling the use of instrumentation through the arm. Navigated instruments are then introduced through the robotic arm into the pedicle, preparing it for screw application, with the robotic arm maintaining a fixed trajectory [ 163 ]. These robots are being utilized both during L-SPS and P-SPS ( Figure 5 ) [ 164 ].…”
Section: Recent Advancesmentioning
confidence: 99%